The Unity, Power and Energy of the Holy Trinity in the Theology of Gregory of Nyssa - Zhukovskyy, Viktor (Studia Ceranea, 2023)
The article discusses the problem of the ontological distinction between God’s transcendence and immanence in the theological thought of Gregory of Nyssa, a Church Father of the 4th century. The author presents the main conceptual and terminological apparatuses that Gregory used in his antinomic approach to the complex interpretation of apophatic and kataphatic images of God. He analyzes the main characteristics of these two dimensions of the nature of God. Special attention is paid to the analysis of the Trinitarian approach in answering the question: how can God, who is completely ontologicaly removed from creation, be at the same time actively present in the world and filling it. In this context the author analyzes the key notions, which express the ontological remoteness of the divine essence of the Holy Trinity and God’s active nearness in relation to created being.